The Relationship of The Level of Information Satisfaction With The Level of Anxiety of Patients' Families In The Icu Room of Mekarsari Hospital, Bekasi, 2025 - Intan Titania Frychillia Dewi; Cusmarih Cusmarih (Jurnal Ners, 2026)
Background The Intensive Care Unit (ICU) is one of the important service units in hospitals that provides intensive care. This unit is supported by trained nurses and adequate medical facilities to carry out monitoring, nursing actions and therapy on patients with critical conditions or life-threatening complications, but who still have the possibility of recovery. Patient care in the intensive care unit has a significant impact on the family, because it creates various forms of burden, including physical, social and cultural aspects. Globally, various studies show that more than 40% to 60% of the families of patients accompanying care in the ICU experience anxiety at a moderate to severe level. Family satisfaction reflects acceptance of the services received, especially in the communication aspect. in the Bekasi City Regional Hospital confirmed a similar pattern, where there was a significant relationship between the level of family understanding regarding the patient's condition and the level of anxiety experienced, indicating that a lack of medical information could increase family anxiety. Research Objective: To determine the relationship between the level of information satisfaction and the level of anxiety of the patient's family in the ICU room at Mekarsari Hospital, Bekasi in 2025.Research Method This research design uses a quantitative research design with a correlational descriptive design, using a cross-sectional approach to identify the relationship between the level of information satisfaction and the level of anxiety of the patient's family in the ICU Room at Mekarsari Hospital, Bekasi. The sampling technique in this research was to use a total sampling technique with a total of 37 respondents. Research Results: The research results show that there is no significant relationship between information satisfaction and the anxiety level of patient families in the ICU room at Mekarsari Hospital, Bekasi in 2025, with a p-value of 0.730 (p > 0.05). Conclusions and Suggestions There is no significant relationship between satisfaction with information and the level of anxiety of the patient's family in the ICU room at Mekarsari Hospital Bekasi in 2025. With the results of this research obtained, it is recommended that future researchers can develop this research by adding other variables that have the potential to influence the anxiety level of the patient's family and using methods and a larger sample size to obtain more comprehensive results.